Genomic study of severe fetal anomalies and discovery of GREB1L mutations in renal agenesis. (July 2018) - Boissel, Sarah; Fallet-Bianco, Catherine; Chitayat, David; Kremer, Valérie; Nassif, Christina; Rypens, Françoise; Delrue, Marie-Ange; Dal Soglio, Dorothée; Oligny, Luc; Patey, Natalie; Flori, Elisabeth; Cloutier, Mireille; et al.
Abstract Purpose Fetal anomalies represent a poorly studied group of developmental disorders. Our objective was to assess the impact of whole-exome sequencing (WES) on the investigation of these anomalies. Methods We performed WES in 101 fetuses or stillborns who presented prenatally with severe anomalies, including renal a/dysgenesis, VACTERL association (vertebral defects, anal atresia, cardiac defects, tracheoesophageal fistula, renal anomalies, and limb abnormalities), brain anomalies, suspected ciliopathies, multiple major malformations, and akinesia. Results A molecular diagnosis was obtained in 19 cases (19%). In 13 of these cases, the diagnosis was not initially suspected by the clinicians because the phenotype was nonspecific or atypical, corresponding in some cases to the severe end of the spectrum of a known disease (e.g., MNX1-, RYR1-, orTUBB- related disorders). In addition, we identified likely pathogenic variants in genes (DSTYK, ACTB, andHIVEP2 ) previously associated with phenotypes that were substantially different from those found in our cases. Finally, we identified variants in novel candidate genes that were associated with perinatal lethality, including de novo mutations inGREB1L in two cases with bilateral renal agenesis, which represents a significant enrichment of such mutations in our cohort. Conclusion Our study opens a window on the distinctive genetic landscape associated with fetal anomalies and highlights the power—but also the challenges—of WES in prenatal diagnosis.